2019
DOI: 10.1021/acssensors.9b00736
|View full text |Cite
|
Sign up to set email alerts
|

Online Monitoring of Solutions Within Microfluidic Chips: Simultaneous Raman and UV–Vis Absorption Spectroscopies

Abstract: Microfluidics is an appealing analytical tool in the global effort to close the nuclear fuel cycle. Using a microfluidic chip permits the analysis of greatly reduced sample volumes compared to what is necessary for traditional analytical methods. There is a commensurate reduction in disposal volume and cost. The development of novel sensors is necessary to take full advantage of the microchip configuration, where optical-spectroscopy-based approaches offer a powerful route to characterize chemical composition.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 38 publications
(66 reference statements)
2
35
0
Order By: Relevance
“…However, previous study has shown that a PLS model can accurately quantify the [Nd 3þ ] even when the [HNO 3 ] varies so long as the variation is represented in the training set. 36,37 This observation can also be applied to other metal ions. Sample spectra were referenced to a deionized water spectrum using the UV-Vis instrumental software before exporting to Matlab for study.…”
Section: Chemometric Modelingmentioning
confidence: 77%
See 1 more Smart Citation
“…However, previous study has shown that a PLS model can accurately quantify the [Nd 3þ ] even when the [HNO 3 ] varies so long as the variation is represented in the training set. 36,37 This observation can also be applied to other metal ions. Sample spectra were referenced to a deionized water spectrum using the UV-Vis instrumental software before exporting to Matlab for study.…”
Section: Chemometric Modelingmentioning
confidence: 77%
“…4 Neodymium has also been used as a non-radioactive surrogate for Pu 3þ and Pu 4þ ion, both spectroscopically and chemically. 36 These properties make Nd 3þ an ideal candidate for chemometric analysis demonstrations. The high absorption band of Cu 2þ at >560 nm as a perturbation of the baseline for the Nd 3þ bands in that region and is also a common contaminant in fuel reprocessing systems.…”
Section: Introductionmentioning
confidence: 99%
“…It was necessary to preprocess the original spectra due to the uneven intensity of light sources at different wavelengths and the influence of instrument noise. In this paper, the spectra were processed using ten preprocessing methods, including multiplicative scatter correction (MSC) [ 23 ], standardized normal variate (SNV) [ 24 ], normalization [ 25 ], autoscales [ 26 ], mean centering (MC) [ 27 ], moving average method (MA) [ 28 ], detrend fluctuation analysis (Detrend) [ 29 ], Savitsky–Golay smoothing (SG) [ 30 ], Savitsky–Golay first derivative (SG-FD) [ 31 ], and Savitsky–Golay second derivative (SG-SD) [ 32 ]. To reduce calculation and increase calculation speed, competitive adaptive reweighted sampling (CARS) [ 33 ], principal components analysis (PCA) [ 34 ], and successive projections algorithm (SPA) [ 35 ] are preferable to extract feature wavelengths to reduce the dimensionality.…”
Section: Methodsmentioning
confidence: 99%
“…It is necessary to preprocess the original spectra due to the uneven intensity of light sources at different wavelengths and the influence of instrument noise. In this paper, the spectra are processed by ten pre-processing methods, including Multiplicative Scatter Correction (MSC) [18], Standardized Normal Variate (SNV) [19], Normalization [20], Autoscales [21], Mean Centering (MC) [22], Moving-Average Method (MA) [23], Detrend Fluctuation Analysis (Detrend) [24], Savitsky-Golay Smoothing (SG) [25], Savitsky-Golay-First Derivative (SG-FD) [26] and Savitsky-Golay-Second Derivative (SG-SD) [27]. to distinguish due to their obvious spoilage and unpleasant smell deterioration, so they will not be discussed in this article.…”
Section: Spectrum Processing Methodsmentioning
confidence: 99%